Guts - Telgemeier, Raina; Colored by Braden Lamb (New York Graphix Logo and Scholastic, 2019)
"Raina wakes up one night with a terrible upset stomach. Her mom has one, too, so it's probably just a bug. Raina eventually returns to school, where she's dealing with the usual highs and lows: friends, not-friends, and classmates who think the school year is just one long gross-out session. It soon becomes clear that Raina's tummy trouble isn't going away ... and it coincides with her worries about food, school, and changing friendships. What's going on?"--Provided by publisher.
Include Color Illustrations
Keywords: Stomach--Diseases -- Children--Physiology -- Stress in children -- Phobias -- Digestion -- Fear in children